2017
DOI: 10.25133/jpssv26n1.004
|View full text |Cite
|
Sign up to set email alerts
|

The Reach of Media to Smokers and Smokeless Tobacco Users in India: Evidence from the Global Adult Tobacco Survey (GATS)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The "contextual effect" emphasizes the significance of the social and demographic composition of people's lives in urban areas [40]. Some previous studies found that higher education leads to lower tobacco consumption [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The "contextual effect" emphasizes the significance of the social and demographic composition of people's lives in urban areas [40]. Some previous studies found that higher education leads to lower tobacco consumption [41][42][43].…”
Section: Discussionmentioning
confidence: 99%